2021
DOI: 10.1007/s10067-021-05793-6
|View full text |Cite
|
Sign up to set email alerts
|

Educational quality of YouTube videos on musculoskeletal ultrasound

Abstract: Introduction/objectives A progressively growing number of rheumatologists have integrated musculoskeletal ultrasound (MSUS) as a prized tool in their daily clinical practice over the past two decades. Lately, YouTube is often used by healthcare professionals as an educational tool. This study aimed to analyze the quality of educational information available on YouTube pertaining to MSUS. Method We performed a search using the keyword “musculoskeletal ultrasound” on YouT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 38 publications
(54 reference statements)
3
35
0
2
Order By: Relevance
“…The DISCERN questionnaire includes five ‘yes’ or ‘no’ questions about video utility and quality, and a ‘yes’ answer equals one point and a ‘no’ answer means zero points. The DISCERN score is obtained by summing the scores for the questions [ 9 ]. The global quality score (GQS) was determined to analyze video quality, and each video was scored from worst to best, between one and five.…”
Section: Methodsmentioning
confidence: 99%
“…The DISCERN questionnaire includes five ‘yes’ or ‘no’ questions about video utility and quality, and a ‘yes’ answer equals one point and a ‘no’ answer means zero points. The DISCERN score is obtained by summing the scores for the questions [ 9 ]. The global quality score (GQS) was determined to analyze video quality, and each video was scored from worst to best, between one and five.…”
Section: Methodsmentioning
confidence: 99%
“…In another study by Duran and Kizilkan on quality analysis of testicular cancer videos on YouTube, the mean video length was reported as 8.86 minutes ( 29 ). In another study by Zengin and Onder, the mean video length was found as 4.21 minutes ( 30 ). The mean video length found in our study was within the range reported by the other studies.…”
Section: Discussionmentioning
confidence: 97%
“…Actually, a default “relevance” sorting option was adopted by many studies when evaluating the reliability and quality of YouTube videos providing medical information to patients ( 22 , 29 , 32 , 57 60 ). The default ranking option—“Relevance”—was the most commonly used option in the YouTube ranking algorithm (relevance, upload date, number of views, rating) ( 61 , 62 ). This search strategy may miss some videos that have low views or hits but may be of high quality, but it is a practical way for casual users of YouTube to obtain information.…”
Section: Discussionmentioning
confidence: 99%